THE CONCEPT OF AGRARIAN REFORM ON THE WELFARE OF FARMERS (CASE STUDY IN TANGERANG REGENCY) - Puspita Sari, Annisa; Amiludin, Amiludin (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
In order to realize Agrarian Reform, Tangerang Regency has implemented a national program which is called as Agrarian Reform Movement, one of which is through asset legality. In fact, the Agrarian Reform Movement program run by Office of Land Affairs in Tangerang Regency regarding asset legality has not run well since there are still problems regarding land, one of which is that many people have not received legal certainty regarding their land rights. The aim of this study is to determine the concept of Complete Systematic Land Registration (PTSL) which is one of the Agrarian Reform schemes from the Agrarian Reform Synergy Movement program and its benefits for farmer welfare. Moreover, the research method used in this study is a qualitative research method with a normative legal approach and data sources obtained from secondary data. The result of this study shows that the implementation of PTSL conducted by the PTSL Adjudication Team in Tangerang Regency has run well in accordance with the target and PTSL certificate which is very beneficial for farmer welfare.